Sundowning in Dementia: Clinical Relevance, Pathophysiological Determinants, and Therapeutic Approaches - Canevelli, Marco; Valletta, Martina; Trebbastoni, Alessandro; Sarli, Giuseppe; D’Antonio, Fabrizia; Tariciotti, Leonardo; de Lena, Carlo; Bruno, Giuseppe (Frontiers in Medicine, 2016)
Sundowning means the emergence or worsening of neuropsychiatric symptoms (NPS) in the late afternoon or early evening. This syndrome has been recognized since a long time in the field of dementing illnesses and is well known among most of healthcare providers involved in the assistance of people with dementia. Indeed, it represents a common manifestation among persons with dementia, and is associated with several adverse outcomes (such as institutionalization, faster cognitive worsening, and greater caregiver burden). Its occurrence and phenotypic characteristics may be influenced by diverse neurobiological, psychosocial, and environmental determinants. Moreover, it may pose diagnostic challenges in relation to other common causes of behavioral disruptions. Beside these considerations, this phenomenon has so far drawn limited clinical and scientific interest compared to other specific NPS occurring in dementias, as indicated by the lack of commonly agreed definitions, specific screening/assessment tools, and robust estimates on its prevalence. Accordingly, no randomized controlled trial (RCT) specifically investigating the effectiveness of pharmacological and non-pharmacological strategies in managing this condition among demented patients has been yet conducted. In the present narrative review we present and discuss available evidence concerning sundowning occurring in people with dementia. A special focus is given to its definitions, pathophysiological determinants, and clinical relevance, as well as to the clinical and therapeutic approaches required for its management in the daily practice.